Wind-PV Hybrid Energy Source Fed Three Level NPC with Quasi Z Source Network - Palanisamy R; Vijayakumar K (International Journal of Power Electronics and Drive Systems (IJPEDS), 2017)
Multilevel inverters find use in industrial drive applications and grid based power generation. Owing to the increasing power demand and rising conventional generation costs a new alternative in renewable energy source is gaining popularity and acceptance. A Wind-PV hybrid renewable energy source is proposed which increases power reliability and improves standalone generation efficiency. A Quasi Z source network allows inverter shoot through possibility while boosting the dc voltage fed to the Neutral Point Clamped MLI. Simulation results were obtained for two levels VSI and further simulations for 3 level quasi NPC-TLI verified using Matlab Simulink and hardware implementation results verified by using DSP controller